Bandwidth Estimation in Wireless Lans for Multimedia Streaming Services - Heung Ki Lee; Varrian Hall; Ki Hwan Yum; Kyoung Ill Kim; Eun Jung Kim (Advances in Multimedia)
The popularity of multimedia streaming services via wireless networks presents major challenges in the management of network bandwidth. One challenge is to quickly and precisely estimate the available bandwidth for the decision of streaming rates of layered and scalable multimedia services. Previous studies based on wired networks are too burdensome to be applied to multimedia applications in wireless networks. In this paper, a new method, IdleGap, is suggested to estimate the available bandwidth of a wireless LAN based on the information from a low layer in the protocol stack. We use a network simulation tool, NS-2, to evaluate our new method with various ranges of cross-traffic and observation times. Our simulation results show that IdleGap accurately estimates the available bandwidth for all ranges of cross-traffic (100 Kbps ∼ 1 Mbps) with a very short observation time of 10 seconds.